2023
DOI: 10.1093/mnras/stad2327
|View full text |Cite
|
Sign up to set email alerts
|

Spectropolarimetric study of 4U 1630−47 in steep power-law state with IXPE and NICER

Divya Rawat,
Akash Garg,
Mariano Méndez

Abstract: We probe the spectropolarimetric properties of the black-hole binary source 4U 1630−47 in the steep power law state. We detect a significant polarization fraction of ∼7 % at a polarization angle of ∼21 ○. The 2-12 keV NICER spectrum can be fitted with a combination of a thermal and a Comptonization component, the latter characterized by a spectral index, Γ ∼2.1, along with a reflection feature at ∼7.0 keV. In the 2–8 keV band, the degree of polarization of 4U 1630−47 in the steep power law state is 4.4 σ diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…IXPE previously observed 4U 1630-47 in the HSS where the detected emission was primarily from the thermal accretion disk (Ratheesh et al 2023, henceforth Paper I;and Kushwaha et al 2023;Rawat et al 2023). That observation revealed that the PD increased with energy from ∼6% at 2 keV to ∼10% at 8 keV.…”
Section: Introductionmentioning
confidence: 87%
“…IXPE previously observed 4U 1630-47 in the HSS where the detected emission was primarily from the thermal accretion disk (Ratheesh et al 2023, henceforth Paper I;and Kushwaha et al 2023;Rawat et al 2023). That observation revealed that the PD increased with energy from ∼6% at 2 keV to ∼10% at 8 keV.…”
Section: Introductionmentioning
confidence: 87%